Francisella novicida Cas9 interrogates genomic DNA with very high specificity and can be used for mammalian genome editing - Acharya, Sundaram; Mishra, Arpit; Paul, Deepanjan; Ansari, Asgar Hussain; Azhar, Mohd; Kumar, Manoj; Rauthan, Riya; Sharma, Namrata; Aich, Meghali; Sinha, Dipanjali; Sharma, Saumya; Jain, Shivani; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2019)
Genome editing using the CRISPR/Cas9 system has been used to make precise heritable changes in the DNA of organisms. Although the widely used Streptococcus pyogenes Cas9 (SpCas9) and its engineered variants have been efficiently harnessed for numerous gene-editing applications across different platforms, concerns remain regarding their putative off-targeting at multiple loci across the genome. Here we report that Francisella novicida Cas9 (FnCas9) shows a very high specificity of binding to its intended targets and negligible binding to off-target loci. The specificity is determined by its minimal binding affinity with DNA when mismatches to the target single-guide RNA (sgRNA) are present in the sgRNA:DNA heteroduplex. FnCas9 produces staggered cleavage, higher homology-directed repair rates, and very low nonspecific genome editing compared to SpCas9. We demonstrate FnCas9-mediated correction of the sickle cell mutation in patient-derived induced pluripotent stem cells and propose that it can be used for precise therapeutic genome editing for a wide variety of genetic disorders.
Keywords: CRISPR Cas9; gene therapy; Genome editing; iPSCs; sickle cell anemia

Rapid and accurate nucleobase detection using FnCas9 and its application in COVID-19 diagnosis - Azhar, Mohd; Phutela, Rhythm; Kumar, Manoj; Ansari, Asgar Hussain; Rauthan, Riya; Gulati, Sneha; Sharma, Namrata; Sinha, Dipanjali; Sharma, Saumya; Singh, Sunaina; Acharya, Sundaram; Sarkar, Sajal; et al. (Biosensors & Bioelectronics, 2021)
Rapid detection of DNA/RNA pathogenic sequences or variants through point-of-care diagnostics is valuable for accelerated clinical prognosis, as witnessed during the recent COVID-19 outbreak. Traditional methods relying on qPCR or sequencing are tough to implement with limited resources, necessitating the development of accurate and robust alternative strategies. Here, we report FnCas9 Editor Linked Uniform Detection Assay (FELUDA) that utilizes a direct Cas9 based enzymatic readout for detecting nucleobase and nucleotide sequences without transcleavage of reporter molecules. We also demonstrate that FELUDA is 100% accurate in detecting single nucleotide variants (SNVs), including heterozygous carriers, and present a simple web-tool JATAYU to aid end-users. FELUDA is semi-quantitative, can adapt to multiple signal detection platforms, and deploy for versatile applications such as molecular diagnosis during infectious disease outbreaks like COVID-19. Employing a lateral flow readout, FELUDA shows 100% sensitivity and 97% specificity across all ranges of viral loads in clinical samples within 1hr. In combination with RT-RPA and a smartphone application True Outcome Predicted via Strip Evaluation (TOPSE), we present a prototype for FELUDA for CoV-2 detection closer to home.
Keywords: CRISPRDx; FELUDA; FnCas9; LFA; SARS-CoV2; SNV detection